RASIONALITAS MUSLIM TERHADAP PERILAKU ISRAF DALAM KONSUMSI PERSPEKTIF EKONOMI ISLAM - Dita Afrina (EkBis: Jurnal Ekonomi dan Bisnis, 2018)
AbstractIn an economic activity, it is prohibited to mix between halal and haram, because this is part of consumption behavior. Seeing how Islamic consumer behavior in consumption is what makes the writer want to analyze the rationality of Israf in consumption by linking the value of values contained in Islamic economics. By using qualitative research methods with literature research, namely by explaining the rationality of Muslims towards israf behavior which will then be explained in the literature on the consumption of Islamic economic perspectives. Where the results of the study show that Muslim rationality is in line with Islamic behavior, by having to consider Israf's actions.Keywords: Rationality, Israf, consumption